Professional experience & the investigative imagination : the art of reflective writing - Winter, Richard, 1943- (Routledge, 1999)
This book explains how creative writing can be used successfully in the context of professional education. It argues that there is a role for this imaginative style in an area that has traditionally favoured a more distanced approach.